The Impact of Merger strategy on human resources management practices - تناي غني دحام; عبد المحسن بتول الكريم (Journal of Economics and Administrative Sciences, 2020)
The current research aims to test the impact of the strategy of merger (as an explanatory variable) in human resources management practices (as a response variable), and the importance of the subject being an important topic that mimics the Iraqi environment, where has seen many mergers that have not been addressed by former researchers in the field. In addition, the future prospects carry many mergers, and the problem of research was the lack of understanding among departments in how to manage the integration and deal with it, on the basis of scientific which reflected negatively on the practices of human resources management, and the research was based on two main hypotheses Six sub-hypotheses emerge to explore the correlation and influence between research variables by analyzing the answers of the research sample, which included sections managers and divisional officials (243) individuals, Data and information were collected using the questionnaire which included 54 items. The data were analyzed using statistical programs. The researcher adopted statistical methods (relative importance, arithmetic mean, standard deviation, Pearson correlation coefficient, simple linear regression). One of the most important conclusions of the research is the interest of the researched companies in the strategies of integration, when they aim to increase their interest in human resources management practices, especially when they use their interest in conflict management to promote their adoption of these practices. In addition, their interest in communication and organizational culture will work on automatic attention to human resources management practices.